PEMBACAAN LINTAS TEKSTUAL NARASI DEWA RUCI DAN WANITA SAMARIA SEBAGAI MODEL TEOLOGI KONTEKSTUAL BAGI MASYARAKAT JAWA - David Eko Setiawan (Manna Rafflesia, 2025)
This study aims to examine the theme of Living Water through a cross-textual reading of the Dewa Ruci narrative in Javanese tradition and the account of Jesus with the Samaritan woman in John 4. Using the cross-textual reading method, this research identifies similarities, differences, and points of convergence between the two narratives. The integration of these meanings is employed to formulate a contextual theology model that combines the biblical message with the symbolic richness of Javanese culture. The findings are expected to contribute to the development of a theology that is relevant, communicative, and rooted in the Javanese cultural context..